Ota Pavel's Reality Effect. The Respresention and Construction of Reality in Literary Journalism - Manak, Vratislav (Civilia, 2022)
This contribution is focusing on the representation and construction of reality in the literary journalism of the czech writer and journalist Ota Pavel. The study analysis the connection between positivism, literary realism and the birth of reportage as a genre. With using of literary structuralism and the concept of the "realist effect", it shows what kind of textual strategies Ota Pavel's reports use to evoke the realist illusion of a direct connection to the actual world - and to fulfil their ambition of a reflexive representation of reality.
Keywords: Ota Pavel; Journalism; Literary journalism; Reportage; Representation of reality; Literary realism; Reality effect